The Prognostic Value of Adjuvant Chemotherapy in Colon Cancer With Solitary Tumor Deposit - Lin, Qiangkang; Zhou, Huizhen; Shi, Si; Lin, Jixu; Yan, Wangxin (Frontiers in Oncology, 2022)
Purpose: To investigate the survival benefit of adjuvant chemotherapy in colon cancer patients with solitary tumor deposit (TD). Methods: The primary study outcomes used in this study were colon cancer-specific survival (CSS) and overall survival (OS). The differences of the distribution of categorical variables in colon cancer patients with solitary tumor deposit according to adjuvant chemotherapy administration were tested using Pearson’s chi-square test. The Kaplan–Meier method was utilized to evaluate CSS and OS. Hazard ratio (HR) and 95% confidence interval (CI) were calculated by building Cox regression models to assess the prognostic value of different demographic and clinicopathological characteristics. Results: A total of 877 TanyN1cM0 colon cancer patients with solitary tumor deposit were identified in our analysis. It was found that OS (75.4% VS. 42.8% for 5-year OS rate, p < 0.001) and CSS (82.9% VS. 69.3% for 5-year CSS rate, p < 0.001) of colon cancer patients with adjuvant chemotherapy administration was significantly better than those without adjuvant chemotherapy administration. Multivariate Cox survival analyses revealed that overall and colon cancer-specific mortality risks of patients with adjuvant chemotherapy administration were decreased by 65.2% (HR = 0.348, 95%CI = 0.259-0.468, p < 0.001) and 58.9% (HR = 0.411, 95%CI = 0.276-0.613, p < 0.001) compared with those without adjuvant chemotherapy administration, respectively. Conclusions: Adjuvant chemotherapy administration could significantly improve OS and CSS in colon cancer patients with solitary tumor deposit. This is the first study to investigate and demonstrate the survival benefit of adjuvant chemotherapy in colon cancer patients with solitary tumor deposit.